Serial cardiac function tests in myocarditis. Issue 728 (June 1986) - Miklozek, C. L.; Kingsley, E. M.; Crumpaker, C. S.; Modlin, J. F.; Royal, H. D.; Come, P. C.; Mark, R.; Abelmann, W. H.
Abstract : Sixteen patients (mean age 27 years, range 16 to 39 years) with the diagnosis of myopericarditis established by strict clinical criteria were evaluated following recovery 0.7 to 4.0 years (mean 2.7 years) later. Evidence of an acute viral infection was present in 44%. During the acute illness, the major clinical manifestations consisted of pericarditis in 10 patients, acute myocardial infarction in 5, right ventricular dysfunction in 5, bundle branch or hemiblock in 4, ventricular arrhythmias in 3, congestive heart failure in 3 and cardiogenic shock and inappropriate sinus tachycardia in one patient each. Holter monitoring, echophonocardiography and radionuclide ventriculography results were abnormal in 57, 67 and 64% of patients respectively. At follow-up, these tests were abnormal in 67, 7 and 73%. Focal wall motion abnormalities were present in five. Seventy-five percent of patients had one or more abnormal tests at last follow-up. Although 8 patients had improved by a scoring system, 5 patients had an increase in the number of abnormal tests, including one who died. These findings indicate that persistent abnormalities following recovery from myopericarditis are not rare and support the hypothesis that the syndrome of dilated cardiomyopathy may be a sequel of myopericarditis.